تحفظ عقل قرآنی احکامات کی روشنی میں تحقیقی جائزہ: Protection of intellect: A Research study in the light of Quranic teachings - Fatima.tuz.zuhra (International Research Journal of Arabic and Islamic Studies, 2024)
This research work is intended to describe the importance of protection of intellect in the light of Quranic commandments, and to highlight those components of shariah that can be used to evolve and defend the intellect, as well as to introduce those guidelines of shariah that can explain the purpose of Quran.Allah Almighty guided man on how to use his wisdom and intellect to protect himself for a better life. To protect wisdom, God has prohibited everything that harms or destroys man's wisdom and causes him to fall from the highest rank of Ashraf-ul-makhlooqat. That is why the shariah forbade and condemned all intoxicating substances. Quran prohibits the use of hypnotics and those sedatives that badly influence the intellect, in order to promote it, offer it the best use, and supply the facilities and needs for its practical use in the world and the hereafter. Therefore, acquiring knowledge is an obligation and its use is the ultimate kind of wisdom. Those who acquire knowledge do employ it are superior to the ignorant. As a good feature of the intellect, the shariah forbids nonproductive and non-profitable knowledge, which redirects man. Similarly, acquiring wisdom with genuine and righteous knowledge, its methods, providing facilities for it, making the world a source of peace, prosperity, and perfection by making it a source of wisdom is the ambition of Shariah. In this article, an attempt has been made to highlight how to protect one's intellect and then the way to promote it to understand Quranic teachings with the feminist approach and subject interpretation.